USE OF PROGESTERONE-3(O-CARBOXYMETHYL OXIME)-HORSERADISH PEROXIDASE IN A SENSITIVE MICROTITRE-PLATE EIA AND ITS APPLICATION TO A VISUAL MEMBRANE EIA OF PROGESTERONE - YOON, DY; SONG, EY; KWON, DH; CHOI, MJ; BYUN, SM; CHOE, IS; CHUNG, TW (MARCEL DEKKER INC, 1995)
A simple method of visual membrane enzyme-immunoassay (EIA) for the detection of progesterone is described. When two types of progesterone-horseradish peroxidase (HRP) tracers were challenged for binding, in the presence of progesterone, to the monoclonal antiprogesterone antibody, 15A, coated on the microtitre plate, the HRP conjugated at the C-3 position (A-ring) of progesterone competed more effectively with progesterone to the binding site of the monoclonal antibody (mAb) than HRP conjugated at the C-11 position of the C-ring. By using this combination of mAb, 15A, and progesterone-3(O-carboxymethyloxime)-HRP (P-3CMO-HRP), we developed a visual membrane EIA system in which free progesterone in the sample could be quantified by the degree of color development. In this system, free progesterone competed with P-3CMO-HRP for binding sites of mAb immobilized on the nitrocellulose membrane. The stable grey color was formed on the surface of membrane for progesterone-negative and no color for progesterone-positive sample using 3,3'-diaminobenzidine (DAB) with Co2+ as an insoluble substrate solution. To examine whether tetramethylbenzidine (TMB) can substitute for DAB in membrane EIA, an experiment was conducted where TMB was used as an insoluble substrate.